Recycling cathode materials for lithium-ion batteries via Hydro-to-Cathode® method - Shim, Jong Hyun (Frontiers in Batteries and Electrochemistry, 2025)
Due to the rising price and limited resource supply chain of Li [NixMnyCoz]O2 (x + y + z = 1) (NMC) cathode material, lithium-ion battery (LIB) recycling technologies have been emerging as the best solution to address the price issue. Mainly, conventional hydrometallurgy processes have been applied to the LIB recycling field in recognition of its value. One remarkable advantage of the hydrometallurgy method is that it serves as a bridge to enable the Hydro-to-Cathode® method. However, using recycled raw materials in the production of precursor cathode materials needs to be studied in parallel with the impurity (dopant) effect. The insufficient selective impurity removal technology leads to unexpected electrochemical properties in the final NMC cathode active material, which can be doped by several different impurities. Consequently, scrutinizing dopant elements (inorganic and organic) is critical if we want to consider the Hydro-to-Cathode® method as a major recycling process of NMC cathode material.